EKSISTENSI OTONOMI DESA PAKRAMAN DI BALI DALAM KERANGKA OTONOMI DAERAH KHUSUSNYA DALAM PENGELOLAAN OBYEK WISATA - I Gusti Ayu Agung Ariani (University of Udayana, 2014)
Traditional village (Pakraman) is an indigenous people who have the authority to manage his own household, and the authority was born out of thevillage so it is often referred to as having genuine autonomy. On the other handwith the establishment of the state covering the entire area of the country wherethe indigenous villages were then raised the issue regarding the implementationof autonomy in relation to the traditional village authorities also state that givesautonomy to the region in accordance with the centralized system that wasfollowed. That's why it is necessary to examine the existence of a traditionalvillage in Bali autonomy within the framework of regional autonomy especially intourist object management. This study were classified in empirical legal research can be seen in thestudy area were selected using purposive sampling method, it can be seen thatinitially the traditional village autonomy is not recognized in the context ofmanaging a tourist object because of the traditional village is not at all involvedin the management of tourist objects. It was only through an uphill battle, evenwith through demonstrations, traditional village involved in the management of atourist attraction. In the original development management involving privateparties as well as third party, then is only managed as a form of cooperationbetween local government and the Desa Pakraman only somewhat proportionaloutcomes assessed, although there are groups of people who do not approve evensueing Bendesa Desa Pakraman. The cooperation in tourism managementproficiency level set forth in a letter of the Collective Agreement between theGovernment and Bendesa Desa Pakraman.